Kelayakan Usaha Ternak Babi di UD Sindi Mandiri Desa Bongan, Kecamatan Tabanan, Kabupaten Tabanan - PARAMARTA, I PUTU TEGUH; ANTARA, I MADE; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Feasibility of Livestock Pigs at UD Sindi Mandiri Bongan Village, Tabanan District One of the sub sector of agriculture is contained in sub-farms. Pigs become one of the most popular animals to be developed in several regions in Indonesia, especially Bali. One pig farm in the province of Bali, located in Tabanan and is located in the center of Tabanan the pig breeding business in UD Sindi Mandiri located at Bongan village, District of Tabanan, Bali. The purpose of this research was conducted to determine the feasibility of financial, non-financial, and constraints - constraints faced by businesses pigs. Pigs effort financially viable if the review of the value frombreak even point, payback period, net present value, net benefit/cost ratio, gross benefit/cost rati , internal rate of return and sensitivity analysis. The non financial businesses pigs feasible if viewed from the technical aspects, marketing aspects, management aspects, legal/law aspects and environmental aspects. While constraints- constraints faced have been overcome by the breeder. Pig breeders need to develop marketing strategies, technology infrastructure in order to be efficient production, increased quality and production can be increased.
Keywords: pigs business; feasibility; constraints